2016
DOI: 10.18203/2319-2003.ijbcp20164759
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of an outbreak of varicella in a village of Goalpara District, India

Abstract: Background: Chickenpox or varicella is a viral disease caused by varicella-zoster virus (VZV) with different complications. Due to traditional belief peoples/villagers avoids treatment and follows some traditional remedies and folk medicine. To change this thinking of villager’s health awareness is mandatory. The main aim of the study was control the outbreak and minimizes the future transmission.Methods: An outbreak was investigated in a village of Goalpara district of Assam, India after getting the permissio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 8 publications
(8 reference statements)
1
1
0
Order By: Relevance
“…The first incidence was reported in mid-March in Atakcorakhas and on April 10th, 2022 in Pitiz village. Similar findings were found in studies done by Pall et al and Malakar et al where they also found the highest number of cases in March and April [ 13 , 14 ]. Interference with the transmission of VZV by high temperature and in dry seasons has been suggested as a possible reason for this seasonal variation [ 15 , 16 ].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The first incidence was reported in mid-March in Atakcorakhas and on April 10th, 2022 in Pitiz village. Similar findings were found in studies done by Pall et al and Malakar et al where they also found the highest number of cases in March and April [ 13 , 14 ]. Interference with the transmission of VZV by high temperature and in dry seasons has been suggested as a possible reason for this seasonal variation [ 15 , 16 ].…”
Section: Discussionsupporting
confidence: 91%
“…According to Malakar et al and Chakraborty et al, people refuse to take treatment for chickenpox and prefer to utilize solely their traditional cures, and this was also noted in our research where the team had difficulty collecting specimens in Pitiz village due to patient refusals. A total of 31 samples were collected from both villages [ 14 , 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…The newborn has a high chance of serious illness if a pregnant woman gets the condition within five days of delivery. 6 Furthermore delaying the onset of chickenpox from childhood to age might be fatal when it is mild. This could result in more frequent or severe herpes zoster in later years than natural conditions.…”
Section: Introductionmentioning
confidence: 99%